2014
DOI: 10.3389/fpsyg.2014.00193
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in attention to faces and bodies in static and dynamic scenes

Abstract: Typically developing individuals show a strong visual preference for faces and face-like stimuli; however, this may come at the expense of attending to bodies or to other aspects of a scene. The primary goal of the present study was to provide additional insight into the development of attentional mechanisms that underlie perception of real people in naturalistic scenes. We examined the looking behaviors of typical children, adolescents, and young adults as they viewed static and dynamic scenes depicting one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…Dynamic changes were observed in infants' attention to a presenter and their actions across time. In all segments of the video clips, infants paid considerable attention to the presenter's face, as might be expected from previous studies when overall looking time has been calculated (Frank et al, 2014(Frank et al, , 2009(Frank et al, , 2012Stoesz & Jakobson, 2014). However, infants increased attention to the face relative to the action with each additional demonstration of the action.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Dynamic changes were observed in infants' attention to a presenter and their actions across time. In all segments of the video clips, infants paid considerable attention to the presenter's face, as might be expected from previous studies when overall looking time has been calculated (Frank et al, 2014(Frank et al, , 2009(Frank et al, , 2012Stoesz & Jakobson, 2014). However, infants increased attention to the face relative to the action with each additional demonstration of the action.…”
Section: Discussionsupporting
confidence: 56%
“…When presented with a dynamic context, attention to faces has also been shown to increase during the first year of life (Frank, Amso, & Johnson, 2014;Frank, Vul, & Johnson, 2009) and then remains present throughout life (Stoesz & Jakobson, 2014). Furthermore, Frank et al (2014) reported that infants' attentional abilities in general are related to how much they attend to faces.…”
Section: Visual Attention When Observing Repeated Actionsmentioning
confidence: 99%
“…In addition, if social rules really were governing gaze allocation in the social groups because of a suspicion that the actors could view the participants, one would also expect that the equally or perhaps even more socially unacceptable behaviour of staring at women’s bodies would also be avoided. A possibly more convincing and non-social interpretation of this finding is suggested by recent research which has demonstrated that a greater proportion of time is spent fixating bodies when passively viewing dynamic scenes containing multiple characters relative to static scenes containing single characters [ 61 ]. These authors attributed this effect to the participants looking away from the heads of the actors in order to reduce cognitive load associated with processing multiple moving faces.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the sensitivity of neurophysiological responses to complex social scenes is now becoming an increasingly recognized topic in affective neuroscience [ 1 , 2 ]. It is also of paramount importance in important fields such as developmental neuroscience [ 3 ] and autism research, where complex social attention deficits are present [ 2 , 4 ]. Moreover, if these responses could be studied at the single or near single-trial level, this might pave the way to develop brain computer interfaces to train social cognition deficits in these disorders, which are characterized by deficits in social attention.…”
Section: Introductionmentioning
confidence: 99%